A Radial Flow Microfluidic Device for Ultra-high-throughput Affinity-based Isolation of Circulating Tumor Cells - Murlidhar, Vasudha (Small, 2014)
Circulating tumor cells (CTCs) are believed to play an important role in metastasis, a process responsible for the majority of cancer-related deaths. But their rarity in the bloodstream makes microfluidic isolation complex and time-consuming. Additionally the low processing speeds can be a hindrance to obtaining higher yields of CTCs, limiting their potential use as biomarkers for early diagnosis. Here we report a high throughput microfluidic technology, the OncoBean Chip, employing radial flow that introduces a varying shear profile across the device enabling efficient cell capture by affinity at high flow rates. The recovery from whole blood was validated with cancer cell lines H1650 and MCF7, achieving a mean efficiency >80% at a throughput of 10 mL hr(−1) in contrast to a flow rate of 1 mL hr(−1) standardly reported with other microfluidic devices. Cells were recovered with a viability rate of 93% at these high speeds, increasing the ability to use captured CTCs for downstream analysis. Broad clinical application was demonstrated using comparable flow rates from blood specimens obtained from breast, pancreatic and lung cancer patients. Comparable CTC numbers were recovered in all the samples at the two flow rates demonstrating the ability of the technology to perform at high-throughputs.